(untitled) (Journal of Health Sciences, 2016)
Introduction: Several studies regarding the association of the ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) K121Q gene polymorphism with the risk of type 2 diabetes mellitus (T2DM) showed inconsistent results. This study aimed to investigate the association of ENPP1 K121Q gene polymorphism with T2DM risk using meta-analysis. The study was limited to the American, European, and African populations.Methods: PubMed and Embase databases were searched for eligible publications. The following information was extracted from each study: name of first author, publication year, country of origin, sample size of cases and controls, and size of each allele. The combined odds ratios (ORs) and 95% confidence intervals (95% CIs) for the association between ENPP1 K121Q gene polymorphism and T2DM risk were assessed using random or fixed effect model. A comprehensive meta-analysis (CMA) 2.0 was used to analyze the data.Results: Nineteen studies (17717 cases/28022 controls) on the association between ENPP1 K121Q gene polymorphism and T2DM risk were included in this meta-analysis. The results indicated that the ENPP1 K121Q gene polymorphism was associated with increased T2DM risk (Q vs. K genetic model, OR 95% CI = 1.11 [1.02–1.22], p = 0.014; QQ vs. KK + KQ, OR 95% CI = 1.14 [1.01–1.23], p = 0.039) and decreased T2DM risk (K vs. Q, OR 95% CI = 0.90 [0.82–1.00], p = 0.014; KK vs. KQ + QQ, OR 95% CI = 0.89 [0.80–0.98], p = 0.024).Conclusions: The results indicate that the ENPP1 K121Q gene polymorphism is associated with the risk of T2DM in the American, European, and African populations.